Čustva in vloga telesa v kontekstu biblijskih zgodb - Centa Strahovnik, Mateja (Bogoslovni vestnik, 2023)
In this article, we focus on Biblical stories and, within them, on the connection between emotions and bodily sensations. We use a cognitive theory of emotions, which understands emotions as based on value judgments. The focus is on stories involving conflict in which emotions, including bodily sensations, are key to conflict resolution and to the orientation toward moral action. In the Bible, emotions play a multifaceted role. They are a natural and essential part of the human experience and of the relationship between man and God. This paper argues that bodily sensations are the building blocks of emotions or play an important role in the formation of emotions. A theology of emotions contributes to an understanding of this aspect of the body that is related to our emotions. The paper shows the hermeneutical potential of these stories for understanding emotions as embodied cognition and their relevance for morality.
Keywords: bible stories; biblijske zgodbe; bodily sensations; cognition; čustva; emotions; spoznanje; telesni občutki; teologija čustev; theology of emotions